2022
DOI: 10.1002/ijfe.2741
|View full text |Cite
|
Sign up to set email alerts
|

Why do corporate social responsibility‐oriented companies opt for bond debt? Evidence from crisis periods

Abstract: Using a large panel of 19,208 listed companies across 40 countries, we investigate the relation between corporate social responsibility (CSR) and bond debt issuance through two main channels: information asymmetry and monitoring. The information asymmetry channel supports that CSR helps firms exhibit more transparency and thereby opt for bond debt. On the other side, the monitoring channel stipulates that CSR makes managers less inclined to engage in value‐diverting activity which makes worthless the scrutiny … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 111 publications
0
6
0
Order By: Relevance
“…It's important to note that each study may have different data sets, variables, and methodologies, which could explain the discrepancies in their results. Therefore, it is advisable to consider the findings of multiple studies when concluding the relationship between discretionary accruals and WACC and to exercise caution when generalizing the findings from any single study (Abbassi et al, 2022). (2009), and Aldamen and Duncan (2013).…”
Section: Main Results Analysismentioning
confidence: 99%
“…It's important to note that each study may have different data sets, variables, and methodologies, which could explain the discrepancies in their results. Therefore, it is advisable to consider the findings of multiple studies when concluding the relationship between discretionary accruals and WACC and to exercise caution when generalizing the findings from any single study (Abbassi et al, 2022). (2009), and Aldamen and Duncan (2013).…”
Section: Main Results Analysismentioning
confidence: 99%
“…Recent research explores many factors influencing debt choice through these two channels. These factors include social trust (Mazumder and Rao, 2023), company culture (Hasan, 2022), distractions by institutional investors (Asamoah et al ., 2022), and ESG performance (Abbassi et al ., 2022; Asimakopoulos et al ., 2023).…”
Section: Related Literature and Hypothesesmentioning
confidence: 99%
“…Considering the complex interaction between firms and debtholders in the lending process, our research helps understand the decision-making process of debtholders and identify potential governance attributes they might prioritize (Abbassi et al ., 2022; Asimakopoulos et al ., 2023). To obtain a more comprehensive understanding, future research should address the impacts of corporate governance reforms on both private and public debt market development, offering further insights into how these practices influence the overall evolution of debt markets.…”
Section: Implications and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Brogi et al (2022) observed that governments and investors increasingly require banks to channel their loans toward socially responsible borrowers; further, the authors showed that ESG scores are linked to better creditworthiness. Notably, better CSR is linked to more transparency, which helps firms in raising debt (Abbassi et al, 2022). Lu and Abeysekera (2021) noted that voluntary CSR disclosure is more common in firms that are more closely monitored by analysts.…”
Section: Nudging Toward Sri: Sustainable Developement and Ethicsmentioning
confidence: 99%